Pengaruh Literasi Keuangan, Pergaulan Teman Sebaya, dan Life Style Terhadap Perilaku Konsumtif Siswa di SMAS Laboratorium Undiksha Singaraja - Yoga, A. A. Gede Putra Perbawa Dharma; Dharmayasa, I Putu Arya (Ekuitas: Jurnal Pendidikan Ekonomi, 2023)
This research aims to determine the influence of financial literacy, peer interactions and life style on student consumptive behavior at SMAS Laboratory Undiksha Singaraja. This research has a quantitative approach, causal research type. The population of this research was students in classes X, XI and the research sample used the Proportional Random Sampling technique, namely 131 respondents. Data was collected through observations, tests and questionnaires which were analyzed through descriptive analysis and multiple linear regression using IBM SPSS Statistics version 21. The results of the research stated that: (1) Financial literacy has a negative effect on students' consumptive behavior at SMAS Laboratory Undiksha Singaraja with Tcount -0.648 < Ttable 1.9882 and Sig. 0.518 > 0.05 therefore H1 is rejected. (2) Peer interactions have a positive and significant effect on students' consumptive behavior at the Undiksha Singaraja Laboratory High School with Tcount 110.343 > Ttable 1.9882 and Sig. 0.000 < 0.05 therefore H2 is accepted. (3) Life style has a positive and significant effect on students' consumptive behavior at SMAS Laboratory Undiksha Singaraja with Tcount 2.040 > Ttable 1.9882 and Sig. 0.043 < 0.05 therefore H3 is accepted. (4) Financial literacy, peer interactions, and life style together have a significant influence on students' consumptive behavior at the Undiksha Singaraja Laboratory High School with Fcount 38.313 > Ftable 2.68 and Sig. 0.000 < 0.05 therefore H4 is accepted. The magnitude of the contribution of financial literacy, peer interactions and life style in influencing student consumptive behavior at the Undiksha Singaraja Laboratory High School is 47.5%.